Health effects of climate change and mitigating effects of climate policies: Evidence from Bangladesh - Shaikh Eskander; Minhaj Uddin Mahmud (Asian Development Bank (ADB), 2024)
This paper explores the mitigating effects of climate policies in addressing climate-induced health adversities. We first investigate the effect of in utero exposure to rainfall variations on child health outcomes in Bangladesh and find that in utero exposure to rainfall variations negatively affects children's anthropometric outcomes. We then exploit the heterogeneity in location and timing of district-level allocations for climate projects under the Bangladesh Climate Change Trust Fund to identify that some of these rainfall-induced health adversities can be mitigated through climate policies. Our findings are robust to alternative empirical specifications and have important policy implications.
Keywords: Q54; Q58; I38; 330; climate change; climate finance; health; rainfall